Heterodox stabilization policies in Latin America - Schuldt, Jurgen (1988)
The article analizes the failure of heterodox stabilization policies that were followed, in the mid eighties, as a reaction to orthodox antiflationary policies designed in economies which were experiencing cronic inflation. The author's message is that this failure is mainly due to incomplete and incoherent programs, as well as to mistakes in their implementation, in contrast to a conceptual vacuum or an inadequate analysis of the situation. In the first part the author covers the explanation given for Latin American inflation by structuralists in the fifties and sixties. In the second part the author focuses on the theorical and practical aspects of the heterodox satabilization policies. Finally, a broad bibliography is included.​